Infinite Servers with Poisson Arrivals Queue Busy Period with PME Distribution - Ferreira, M. A. M. (arXiv:2110.08053, 2025)
In this article it is shown that if the busy period of a MGinf queue system is PME distributed, the service time is a random variable with a long tail distribution. The result is obtained through Laplace transforms analysis